Resource recovery from organic wastes using Black Soldier Fly Larvae - Matheka, Rosemary; Raude, James Messo; Murunga, Sylvia (African Journal of Science, Technology and Social Sciences, 2022)
Solid waste management is a cross-cutting issue impacting many aspects of the environment, society and economic development. Cities of low- and middle-income countries are currently facing severe challenges in management of the increasing amount of solid waste produced, particularly the organic waste fraction. This review presents information in literature about the utilization of Black soldier fly (BSF) in managing organic waste. It summarizes the approaches in organic waste management, use of BSF in organic waste management, life cycle and growth conditions of BSF and the benefits of utilizing BSF for resource recovery. Organic waste treatment using BSF is an emerging waste management technology with minimal global warming potential. The BSF larvae helps in carbon sequestration and is a protein source which can help alleviate the raising global demand for animal feed. The BSF larval model provides for nutrient recycling, waste reduction and value addition significantly contributing to economic viability, competitiveness and strategic development in environmental management and agriculture.